A method for preparing an impact-resistant polycrystalline diamond compact with reduced residual stress

CN122999990APending Publication Date: 2026-10-30JIANGXI TUNGSTEN NEW MATERIALS INNOVATION RESEARCH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611141332.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但这种方法的应力释放效率较低,退火后仍有较大应力残留,还可能引起金刚石石墨化,影响PDC的力学性能

Benefits of technology

[0023]本发明具有以下的有益效果:本发明中的梯度过渡层由碳化钨、金刚石和黏结相组成,将原本集中于界面的突变应力分散至整个梯度过渡层中,从而减小剪应力集中,提高界面结合强度与抗冲击性能。本发明在高温高压合成后,对PDC进行冷-热的冷热交替循环处理;冷处理使复合片整体温度骤降,在表层预先建立有益的压应力状态,再通过热处理使聚晶金刚石层、梯度过渡层及硬质合金基体内部的热错配应力通过晶界滑移和微观塑性变形得到充分释放,如此循环处理,可以避免单一热处理可能引起的应力回弹或相变开裂。经该循环处理后,PDC内部的残余应力可降至极低水平,显著提高了复合片的抗冲击性能和服役寿命,且工艺简单、成本低,易于工业化实施。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999990A_ABST
    Figure CN122999990A_ABST
Patent Text Reader

Abstract

The application relates to the field of superhard materials, in particular to a preparation method of an impact-resistant polycrystalline diamond compact with reduced residual stress, which comprises the following steps: tabletting of a polycrystalline diamond layer powder raw material, a gradient transition layer block and a hard alloy by a six-surface press, high-temperature and high-pressure sintering, and alternately placing in a cold environment and a hot environment for circulation after sintering; the cold environment is below-180 DEG C, and the hot environment is 400 DEG C-800 DEG C. The gradient transition layer is composed of tungsten carbide, diamond and a binder phase, and the sudden stress originally concentrated on the interface is dispersed to the whole gradient transition layer, so that the shear stress concentration is reduced, the interface bonding strength and the impact resistance are improved; after high-temperature and high-pressure synthesis, cold and hot cycle treatment can avoid stress rebound or phase change cracking caused by single heat treatment; the residual stress can be reduced to an extremely low level, and the impact resistance and service life of the compact are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of superhard materials, and specifically to a method for preparing polycrystalline diamond composite sheets. Background Technology

[0002] Polycrystalline diamond compacts (PDCs) possess high hardness and wear resistance, and are widely used in oil and gas drilling, mining, and high-end machining. PDCs are made by sintering a cemented carbide substrate and a polycrystalline diamond layer under high temperature and pressure. Due to the significant difference in the coefficients of thermal expansion between diamond and cemented carbide, substantial residual stress is generated, and this residual stress increases further with increasing high-temperature and high-pressure synthesis conditions. Residual stress has a significant adverse effect on the performance of PDCs. The most direct impact is a reduction in impact toughness, shortening the service life of PDCs. Furthermore, it weakens the wear resistance and thermal stability of PDCs.

[0003] To reduce residual stress, long-duration high-temperature annealing is currently the main technique used. However, this method has low stress release efficiency, leaving significant residual stress after annealing and potentially causing diamond graphitization, which affects the mechanical properties of PDC. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a method for preparing an impact-resistant polycrystalline diamond composite sheet that can reduce residual stress.

[0005] The technical solution adopted by this invention to solve its technical problem is as follows: A method for preparing an impact-resistant polycrystalline diamond composite sheet with reduced residual stress, comprising: compacting polycrystalline diamond powder raw material, gradient transition layer block, and cemented carbide to form a sheet; assembling the sheet into a composite block of a six-sided press, and subjecting it to high-temperature and high-pressure sintering at 5GPa~8GPa and 1300~1700℃; after sintering, alternatingly placing it in a cold environment and a hot environment for more than two cycles to obtain the final product; the resulting polycrystalline diamond composite sheet comprises, in sequence: a polycrystalline diamond layer, a gradient transition layer, and a cemented carbide layer; The cold environment is -180℃ to -210℃; the hot environment is 400℃ to 800℃. The polycrystalline diamond layer contains more than 90% diamond by volume; the polycrystalline diamond layer also includes a metallic binder phase. The main components of the gradient transition layer are diamond, tungsten carbide and a metal binder phase.

[0006] Preferably, the powder raw materials of the polycrystalline diamond layer include: diamond powder A with a median particle size of 10μm to 20μm, diamond powder B with a median particle size of 1μm to 5μm, and metal binder phase powder.

[0007] Preferably, in the powder raw material of the polycrystalline diamond layer, the total volume fraction of diamond powder A and B is greater than 90%; and the volume fraction of metal binder powder is less than 10%.

[0008] Preferably, in the powder raw material of the polycrystalline diamond layer, the volume ratio of diamond powder A to diamond powder B is 2~6:1.

[0009] Preferably, the gradient transition layer can be subdivided into 2 to 5 sub-layers according to its composition. The sub-layers closer to the polycrystalline diamond layer have a higher diamond content and a lower content of tungsten carbide and metal binder phase. The sub-layers closer to the cemented carbide layer have a lower diamond content and a higher content of tungsten carbide and metal binder phase.

[0010] Preferably, the content of each component in each sublayer conforms to the following formula: ; in, The total number of sub-layers is denoted by , with the sub-layer closest to the polycrystalline diamond layer designated as the first sub-layer, and all sub-layers are numbered sequentially. The sequence number of the sub-layer. Not greater than Positive integers; For the first Volume fraction of a certain component in a sublayer This represents the volume fraction of this component in the polycrystalline diamond layer. This represents the volume fraction of this component in the cemented carbide layer.

[0011] Preferably, the gradient transition layer block is prepared by first printing a green blank using a binder spraying additive manufacturing process, and then achieving debinding and densification through vacuum hot pressing sintering to obtain the gradient transition layer block.

[0012] Preferably, the raw materials used in the binder spraying additive manufacturing process include: diamond powder with a median particle size of 10μm to 20μm, tungsten carbide powder with a median particle size of 1.2μm to 2.0μm, and metal binder phase powder with a median particle size of 1μm to 5μm.

[0013] Preferably, the temperature for vacuum hot pressing sintering is 750~850℃.

[0014] Preferably, the metal binder powder is a cobalt-based alloy powder with a median particle size of 1 μm to 5 μm.

[0015] Preferably, the metal binder phase is mainly composed of cobalt, and by mass percentage, it also includes: 10%~30% nickel, 5%~10% iron, less than 5% chromium, less than 5% titanium, and less than 2% boron.

[0016] Preferably, the mass fraction of cobalt in the cemented carbide is 10% to 15%.

[0017] Preferably, the thickness of the polycrystalline diamond layer is 2~4 mm.

[0018] Preferably, the thickness of the gradient transition layer is 1~3mm.

[0019] Preferably, the thickness of the cemented carbide layer is 5~20mm.

[0020] Preferably, the single placement time in a cold environment is 0.5 to 2 hours.

[0021] Preferably, the single placement time in a thermal environment is 0.5 to 2 hours.

[0022] Preferably, the high-temperature and high-pressure sintering time is 5 to 20 minutes.

[0023] This invention offers the following advantages: The gradient transition layer, composed of tungsten carbide, diamond, and a binder phase, disperses the abrupt stress originally concentrated at the interface throughout the gradient transition layer, thereby reducing shear stress concentration and improving interfacial bonding strength and impact resistance. After high-temperature, high-pressure synthesis, the PDC undergoes a cold-hot alternating cycle treatment. The cold treatment causes a rapid drop in the overall temperature of the composite sheet, establishing a beneficial compressive stress state on the surface. Then, the heat treatment allows the thermal mismatch stress within the polycrystalline diamond layer, gradient transition layer, and cemented carbide matrix to be fully released through grain boundary slip and microscopic plastic deformation. This cyclic treatment avoids stress rebound or phase transformation cracking that might occur with a single heat treatment. After this cyclic treatment, the residual stress inside the PDC can be reduced to an extremely low level, significantly improving the impact resistance and service life of the composite sheet. Furthermore, the process is simple, low-cost, and easily implemented industrially.

[0024] In addition to the objectives, features, and advantages described above, the present invention has other objectives, features, and advantages. The invention will now be described in further detail with reference to the accompanying drawings. Attached Figure Description

[0025] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 -a and Figure 1 -b are scanning electron microscope (SEM) microstructure images of the cross-sections of the polycrystalline diamond composite sheets obtained in Examples 1 and 2 of this invention, respectively. Detailed Implementation

[0026] To make the objectives, solutions, and beneficial technologies of this invention clearer, the invention will be further described in detail below with reference to embodiments and accompanying drawings. It should be noted that the embodiments described in this specification are merely illustrative of the invention and are not intended to limit the invention.

[0027] For simplicity, this paper only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, just as any upper limit can be combined with any other upper limit to form an undefined range. Furthermore, although not explicitly stated, every point or individual value between the endpoints of a range is included within that range. Therefore, each point or individual value can serve as its own lower or upper limit and be combined with any other point or individual value, or with other lower or upper limits, to form an undefined range.

[0028] In this description, it should be noted that, unless otherwise stated, "above" and "below" include the stated number, "multiple" in "one or more" means two or more, and "more than" in "one or more" means two or more.

[0029] The present invention provides a method for preparing an impact-resistant polycrystalline diamond composite sheet with reduced residual stress, comprising: compacting polycrystalline diamond powder raw material, gradient transition layer block, and cemented carbide to form a sheet; assembling the sheet into a composite block in a six-sided press, and subjecting it to high-temperature and high-pressure sintering at 5GPa~8GPa and 1300~1700℃; after sintering, alternating between cold and hot environments for more than two cycles to obtain the final product; the resulting polycrystalline diamond composite sheet comprises, in the thickness direction, a polycrystalline diamond layer, a gradient transition layer, and a cemented carbide layer. The cold environment is -180℃ to -210℃; the hot environment is 400℃ to 800℃. The polycrystalline diamond layer contains more than 90% diamond by volume; the polycrystalline diamond layer also includes a metallic binder phase. The main components of the gradient transition layer are diamond, tungsten carbide and a metal binder phase.

[0030] A gradient transition layer between the polycrystalline diamond (PDC) layer and the cemented carbide (CLC) substrate can significantly reduce the residual stress in PDC. The principle is mainly achieved by using a multi-layered structure, with each layer employing a different ratio of diamond to CLC, resulting in a smooth transition in the coefficient of thermal expansion between layers, thereby reducing residual stress. In this invention, the gradient transition layer consists of tungsten carbide, diamond, and a binder phase, dispersing the abrupt stress originally concentrated at the interface throughout the entire gradient transition layer, thus reducing shear stress concentration and improving interfacial bonding strength and impact resistance.

[0031] This invention involves alternating cryogenic and annealing cycles of PDC (polycrystalline diamond) synthesis followed by high-temperature, high-pressure synthesis. The cryogenic environment causes a rapid drop in the overall temperature of the composite sheet, establishing a beneficial compressive stress state on the surface. Subsequent annealing then allows the thermal mismatch stress within the polycrystalline diamond layer, gradient transition layer, and cemented carbide matrix to be fully released through grain boundary slip and microscopic plastic deformation. This cyclic process avoids stress rebound or phase transformation cracking that might occur with a single heat treatment. After this cyclic treatment, the residual stress within the PDC can be reduced to an extremely low level, significantly improving the impact resistance and service life of the composite sheet. Furthermore, the process is simple, low-cost, and easily implemented industrially.

[0032] In some embodiments of the present invention, the cold environment is a liquid nitrogen environment. A liquid nitrogen environment is typically -180°C to -210°C.

[0033] In some embodiments of the present invention, after high-temperature and high-pressure sintering is completed, the composite sheet is removed, excess material on the surface is removed, and it is ground to a regular shape.

[0034] In some embodiments of the present invention, the powder raw material of polycrystalline diamond layer, the gradient transition layer block, and the cemented carbide are sequentially loaded into a covered metal container, compacted, and made into a tablet.

[0035] In some embodiments of the present invention, the powdered raw material of the polycrystalline diamond layer is first loaded into a metal container, flattened and compacted, and then the gradient transition layer block and hard alloy are placed in sequence, covered with a metal cover, and compacted with a press to form a tablet.

[0036] In some embodiments of the present invention, the powder raw materials of the polycrystalline diamond layer include: diamond powder A with a median particle size of 10μm to 20μm, diamond powder B with a median particle size of 1μm to 5μm, and metal binder phase powder.

[0037] In some embodiments of the present invention, the total volume fraction of diamond powder A and B in the powder raw material of the polycrystalline diamond layer is greater than 90%, and the volume fraction of metal binder powder is less than 10%.

[0038] In some embodiments of the present invention, the volume ratio of diamond powder A to diamond powder B in the powder raw material of the polycrystalline diamond layer is 2~6:1. Studies have found that PDC prepared from coarse powder has good impact toughness, while PDC prepared from fine powder has good wear resistance. When the two are mixed in a certain proportion, the fragmentation of diamond during high-temperature and high-pressure sintering can be significantly suppressed, the integrity of diamond can be maintained, the advantages of coarse and fine diamond powder can be fully utilized, and the wear resistance and impact toughness of PDC can be comprehensively improved.

[0039] In some embodiments of the present invention, the gradient transition layer can be subdivided into 2 to 5 smaller layers according to its composition. The smaller layers closer to the polycrystalline diamond layer have a higher diamond content and lower tungsten carbide and metal binder phase content; the smaller layers closer to the cemented carbide layer have a lower diamond content and higher tungsten carbide and metal binder phase content. The gradient transition layer of the present invention is composed of tungsten carbide, diamond, and a binder phase, and the diamond content decreases gradually from the diamond layer to the cemented carbide layer, while the tungsten carbide and binder phase content increases gradually. Therefore, the coefficient of thermal expansion of each layer increases progressively along the thickness direction, dispersing the abrupt stress originally concentrated at the interface throughout the entire gradient transition layer, thereby reducing shear stress concentration and improving interfacial bonding strength and impact resistance.

[0040] In some embodiments of the present invention, the content of each component in each sublayer conforms to the following formula: ; in, The total number of sub-layers is denoted by , with the sub-layer closest to the polycrystalline diamond layer designated as the first sub-layer, and all sub-layers are numbered sequentially. The sequence number of the sub-layer. Not greater than Positive integers; For the first Volume fraction of a certain component in a sublayer This represents the volume fraction of this component in the polycrystalline diamond layer. This represents the volume fraction of this component in the cemented carbide layer.

[0041] In some embodiments of the present invention, the gradient transition layer block is prepared by first printing a green blank using a binder jet additive manufacturing process, and then achieving debinding and densification through vacuum hot pressing sintering to obtain the gradient transition layer block. There are generally two methods for preparing the gradient transition layer: the first involves sequentially layering mixed powders with varying compositional gradients during powder loading; this method is inefficient and the uniformity of powder layering is difficult to guarantee, which is detrimental to ensuring consistent product performance. The second method uses additive manufacturing technology to prepare cemented carbide with a compositional gradient, but this suffers from low alloy density and unstable performance. This solution uses a binder jet additive manufacturing process to print the gradient transition layer layer by layer, which can precisely control the continuous change of composition in each layer, thereby eliminating stress concentration at the traditional PDC interface. Subsequently, debinding and densification are completed through vacuum rapid hot pressing sintering, achieving binder removal and gradient layer densification. This combined technology not only ensures the accuracy of the compositional distribution and interlayer bonding strength of the gradient layer, but also ensures the density of the gradient layer. By precisely controlling the powder composition of each layer, the defects of uneven powder spreading in traditional methods are overcome, thereby significantly improving the consistency and stability of PDC product performance in different batches and locations.

[0042] In some embodiments of the present invention, the raw materials used in the binder spraying additive manufacturing process include: diamond powder with a median particle size of 10 μm to 20 μm, tungsten carbide powder with a median particle size of 1.2 μm to 2.0 μm, and metal binder phase powder with a median particle size of 1 μm to 5 μm.

[0043] In some embodiments of the present invention, the temperature of vacuum hot pressing sintering is 750~850°C.

[0044] In some embodiments of the present invention, the metal binder powder is a cobalt-based alloy powder with a median particle size of 1 μm to 5 μm.

[0045] In some embodiments of the present invention, the metal binder phase is mainly composed of cobalt, and by mass percentage, it further comprises: 10%~30% nickel, 5%~10% iron, less than 5% chromium, less than 5% titanium, and less than 2% boron. The powder contains nickel and iron, and optionally chromium, titanium, and boron; wherein, nickel and iron not only enhance the ability of the metal binder phase to catalyze the formation of the diamond framework, but also reduce the melting point of the binder phase through alloying; boron can further reduce the melting point of the binder phase and improve the thermal stability of the PDC; chromium and titanium can form carbides at the interface between diamond and the binder phase, thereby enhancing the interfacial bonding strength and hindering microcrack propagation. Overall, the binder phase composition used in the present invention, on the one hand, promotes the formation of the diamond framework and improves the interfacial bonding strength between diamond and the binder phase, thereby enhancing the mechanical properties of the PDC; on the other hand, the binder phase has a low melting point, which can effectively reduce the sintering temperature during subsequent vacuum rapid hot pressing sintering, avoiding graphitization of diamond in the gradient transition layer. Furthermore, the residual stress in PDC originates from the difference in cooling shrinkage rates between the metal and diamond after solidification. During the cooling stage of high-temperature and high-pressure synthesis, the binder phase component of this invention lowers the liquidus temperature, causing the binder phase to begin solidifying at a lower temperature, thereby reducing the thermal stress caused by the difference in thermal shrinkage coefficients between diamond and the binder phase.

[0046] In some embodiments of the present invention, the mass fraction of cobalt in the cemented carbide is 10% to 15%.

[0047] In some embodiments of the present invention, the cemented carbide comprises tungsten carbide and a metallic binder phase.

[0048] In some embodiments of the present invention, the thickness of the polycrystalline diamond layer is 2-4 mm.

[0049] In some embodiments of the present invention, the thickness of the gradient transition layer is 1~3mm.

[0050] In some embodiments of the present invention, the thickness of the cemented carbide layer is 5-20 mm.

[0051] In some embodiments of the present invention, the single placement time in a cold environment is 0.5 to 2 hours.

[0052] In some embodiments of the present invention, the single placement time in a thermal environment is 0.5 to 2 hours.

[0053] In some embodiments of the present invention, the high-temperature and high-pressure sintering time is 5 to 20 minutes.

[0054] Example The following examples describe the disclosure of this invention in more detail. These examples are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of this disclosure. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight. Unless otherwise stated, all reagents used in the examples are available commercially or synthesized using conventional methods and are ready for use without further processing. Unless otherwise stated, all instruments used in the examples are commercially available.

[0055] Example 1 This embodiment relates to a method for preparing an impact-resistant polycrystalline diamond composite sheet with reduced residual stress. The resulting polycrystalline diamond composite sheet comprises, in the thickness direction, a polycrystalline diamond layer, a gradient transition layer, and a cemented carbide layer. In the cemented carbide layer, the volume fraction of tungsten carbide is 79.2%, and the volume fraction of the metallic binder phase is 20.8%. The polycrystalline diamond layer comprises diamond and a metal binder phase, with the diamond volume fraction being 97% and the metal binder phase volume fraction being 3%. The main components of the gradient transition layer are diamond, tungsten carbide, and a metallic binder phase. The gradient transition layer can be further subdivided into two smaller layers based on its composition. The smaller layer closer to the polycrystalline diamond layer has a higher diamond content and a lower content of tungsten carbide and metallic binder phase. The smaller layer closer to the cemented carbide layer has a lower diamond content and a higher content of tungsten carbide and metallic binder phase.

[0056] The content of each component in each sublayer conforms to the following formula: ; in, The total number of sub-layers is denoted by , with the sub-layer closest to the polycrystalline diamond layer designated as the first sub-layer, and all sub-layers are numbered sequentially. The sequence number of the sub-layer. Not greater than Positive integers; For the first Volume fraction of a certain component in a sublayer This represents the volume fraction of this component in the polycrystalline diamond layer. This represents the volume fraction of the component in the cemented carbide layer. In this embodiment, the contents of each component in the first sublayer are: diamond volume fraction 64.67%, binder phase volume fraction 8.93%, and tungsten carbide volume fraction 26.4%; the contents of each component in the second sublayer are: diamond volume fraction 32.33%, binder phase volume fraction 14.87%, and tungsten carbide volume fraction 52.8%.

[0057] The composition of the metal binder phase, by mass percentage, includes: 50% cobalt, 30% nickel, 10% iron, 4% chromium, 4% titanium, and 2% boron.

[0058] The preparation method of the impact-resistant polycrystalline diamond composite sheet with reduced residual stress in this embodiment includes the following specific steps: Weigh out the powder raw materials of the polycrystalline diamond layer and mix them for later use; the powder raw materials of the polycrystalline diamond layer include: diamond powder A with a median particle size of 15μm, diamond powder B with a median particle size of 2μm, and metal binder powder with a median particle size of 3μm; by volume ratio, diamond powder A: diamond powder B: metal binder powder = 73:24:3. A gradient transition layer bulk was prepared; raw material powders for each sublayer were formulated, and a green body was formed by binder jet additive manufacturing process. The thickness of the first sublayer was 0.5 mm, and the thickness of the second sublayer was 0.5 mm. The green body was degreased and densified by vacuum hot pressing sintering at 750℃ to obtain the gradient transition layer bulk body. The raw materials used in the binder jet additive manufacturing process included: diamond powder with a median particle size of 15 μm, tungsten carbide powder with a median particle size of 1.6 μm, and metal binder phase powder with a median particle size of 3 μm. Polycrystalline diamond composite sheets were prepared by loading polycrystalline diamond powder into a metal cup, flattening and compacting it to a height of 2 mm, then loading a sintered gradient transition layer block, followed by cemented carbide (20 mm thick), covering with a metal cap, and compacting it with a press. The composite sheet was then assembled with salt tubes, graphite tubes, pyrophyllite, and other components to form a composite block. The composite block was placed in the synthesis chamber of a six-sided press and subjected to high-temperature, high-pressure sintering at a pressure of 6.5 GPa, a temperature of 1550 °C, and a sintering time of 10 minutes. After sintering, the sheet was removed, excess material was removed from the surface, and the surface was ground smooth. Release the residual stress inside; place it in a container, then place the container in a liquid nitrogen pool (-196℃), leave it for 1 hour, then take it out, then place the container in an annealing furnace at a temperature of 500℃, keep it at that temperature for 1 hour, and take it out. This is one cold and hot cycle; repeat the cold and hot cycle 3 times to obtain an impact-resistant polycrystalline diamond composite sheet with low residual stress.

[0059] Example 2 This embodiment relates to a method for preparing an impact-resistant polycrystalline diamond composite sheet with reduced residual stress. The resulting polycrystalline diamond composite sheet comprises, in the thickness direction, a polycrystalline diamond layer, a gradient transition layer, and a cemented carbide layer. In the cemented carbide layer, the volume fraction of tungsten carbide is 79.2%, and the volume fraction of the metallic binder phase is 20.8%. The polycrystalline diamond layer comprises diamond and a metal binder phase, with the diamond volume fraction being 97% and the metal binder phase volume fraction being 3%. The main components of the gradient transition layer are diamond, tungsten carbide, and a metallic binder phase. The gradient transition layer can be subdivided into three sub-layers according to its composition. The sub-layers closer to the polycrystalline diamond layer have a higher diamond content and a lower content of tungsten carbide and metallic binder phase. The sub-layers closer to the cemented carbide layer have a lower diamond content and a higher content of tungsten carbide and metallic binder phase.

[0060] The content of each component in each sublayer conforms to the following formula: ; in, The total number of sub-layers is denoted by , with the sub-layer closest to the polycrystalline diamond layer designated as the first sub-layer, and all sub-layers are numbered sequentially. The sequence number of the sub-layer. Not greater than Positive integers; For the first Volume fraction of a certain component in a sublayer This represents the volume fraction of this component in the polycrystalline diamond layer. This represents the volume fraction of this component in the cemented carbide layer. In this embodiment, The composition of the first sublayer is as follows: diamond volume fraction 72.75%, binder phase volume fraction 7.45%, and tungsten carbide volume fraction 19.8%. The composition of the second sublayer is as follows: diamond volume fraction 48.5%, binder phase volume fraction 11.9%, and tungsten carbide volume fraction 39.6%. The composition of the third sublayer is as follows: diamond volume fraction is 24.25%, binder phase volume fraction is 16.35%, and tungsten carbide volume fraction is 59.4%.

[0061] The composition of the metal binder phase, by mass percentage, includes: 60% cobalt, 20% nickel, 10% iron, 5% chromium, 4% titanium, and 1% boron.

[0062] The preparation method of the impact-resistant polycrystalline diamond composite sheet with reduced residual stress in this embodiment includes the following specific steps: Weigh out the powder raw materials for the polycrystalline diamond layer and mix them for later use; the powder raw materials for the polycrystalline diamond layer include: diamond powder A with a median particle size of 20 μm, diamond powder B with a median particle size of 3 μm, and metal binder powder with a median particle size of 2 μm; by volume ratio, diamond powder A: diamond powder B: metal binder powder = 75:22:3. A gradient transition layer bulk was prepared; raw material powders for each sublayer were formulated, and a green body was formed by binder jet additive manufacturing process. The thickness of the first sublayer was 0.3 mm, the second sublayer was 0.3 mm, and the third sublayer was 0.4 mm. The green body was degreased and densified by vacuum hot pressing sintering at 800℃ to obtain the gradient transition layer bulk body. The raw materials used in the binder jet additive manufacturing process included: diamond powder with a median particle size of 20 μm, tungsten carbide powder with a median particle size of 2.0 μm, and metal binder phase powder with a median particle size of 2 μm. Polycrystalline diamond composite sheets were prepared by loading polycrystalline diamond powder into a metal cup, flattening and compacting it to a height of 2 mm, then loading a sintered gradient transition layer block, followed by cemented carbide (10 mm thick), covering with a metal cap, and compacting it with a press. The composite sheet was then assembled with salt tubes, graphite tubes, pyrophyllite, and other components into a composite block. The composite block was placed in the synthesis chamber of a six-sided press and subjected to high-temperature, high-pressure sintering at a pressure of 7 GPa, a temperature of 1500℃, and a sintering time of 15 minutes. After sintering, the sheet was removed, excess material was removed from the surface, and the surface was ground smooth. Release the residual stress inside; place it in a container, then place the container in a liquid nitrogen pool (-196℃), leave it for 1 hour, then take it out, then place the container in an annealing furnace at a temperature of 500℃, keep it at that temperature for 1 hour, and take it out. This is one cold and hot cycle; repeat the cold and hot cycle 3 times to obtain an impact-resistant polycrystalline diamond composite sheet with low residual stress.

[0063] Example 3 This embodiment relates to a method for preparing an impact-resistant polycrystalline diamond composite sheet with reduced residual stress. The resulting polycrystalline diamond composite sheet comprises, in the thickness direction, a polycrystalline diamond layer, a gradient transition layer, and a cemented carbide layer. In the cemented carbide layer, the volume fraction of tungsten carbide is 79.2%, and the volume fraction of the metallic binder phase is 20.8%. The polycrystalline diamond layer comprises diamond and a metal binder phase, with the diamond volume fraction being 97% and the metal binder phase volume fraction being 3%. The main components of the gradient transition layer are diamond, tungsten carbide, and a metallic binder phase. The gradient transition layer can be subdivided into three sub-layers according to its composition. The sub-layers closer to the polycrystalline diamond layer have a higher diamond content and a lower content of tungsten carbide and metallic binder phase. The sub-layers closer to the cemented carbide layer have a lower diamond content and a higher content of tungsten carbide and metallic binder phase.

[0064] The content of each component in each sublayer conforms to the following formula: ; in, The total number of sub-layers is denoted by , with the sub-layer closest to the polycrystalline diamond layer designated as the first sub-layer, and all sub-layers are numbered sequentially. The sequence number of the sub-layer. Not greater than Positive integers; For the first Volume fraction of a certain component in a sublayer This represents the volume fraction of this component in the polycrystalline diamond layer. This represents the volume fraction of this component in the cemented carbide layer. In this embodiment, The composition of the first sublayer is as follows: diamond volume fraction 72.75%, binder phase volume fraction 7.45%, and tungsten carbide volume fraction 19.8%. The composition of the second sublayer is as follows: diamond volume fraction 48.5%, binder phase volume fraction 11.9%, and tungsten carbide volume fraction 39.6%. The composition of the third sublayer is as follows: diamond volume fraction is 24.25%, binder phase volume fraction is 16.35%, and tungsten carbide volume fraction is 59.4%.

[0065] The composition of the metal binder phase, by mass percentage, includes: 70% cobalt, 15% nickel, 7% iron, 3% chromium, 3% titanium, and 2% boron.

[0066] The preparation method of the impact-resistant polycrystalline diamond composite sheet with reduced residual stress in this embodiment includes the following specific steps: Weigh out the powder raw materials of the polycrystalline diamond layer and mix them for later use; the powder raw materials of the polycrystalline diamond layer include: diamond powder A with a median particle size of 10 μm, diamond powder B with a median particle size of 2 μm, and metal binder powder with a median particle size of 1 μm; by volume ratio, diamond powder A: diamond powder B: metal binder powder = 70:27:3. A gradient transition layer bulk was prepared; raw material powders for each sublayer were formulated, and a green body was formed by binder jet additive manufacturing process. The thickness of the first sublayer was 0.3 mm, the second sublayer was 0.3 mm, and the third sublayer was 0.4 mm. The green body was degreased and densified by vacuum hot pressing sintering at 850℃ to obtain the gradient transition layer bulk body. The raw materials used in the binder jet additive manufacturing process included: diamond powder with a median particle size of 10 μm, tungsten carbide powder with a median particle size of 1.6 μm, and metal binder phase powder with a median particle size of 1 μm. Polycrystalline diamond composite sheets were prepared by loading polycrystalline diamond powder into a metal cup, flattening and compacting it to a height of 2 mm, then loading a sintered gradient transition layer block, followed by cemented carbide (5 mm thick), covering with a metal cap, and compacting it with a press. The composite sheet was then assembled with salt tubes, graphite tubes, pyrophyllite, and other components into a composite block. The composite block was placed in the synthesis chamber of a six-sided press and subjected to high-temperature, high-pressure sintering at a pressure of 7.7 GPa, a temperature of 1450 °C, and a sintering time of 20 minutes. After sintering, the sheet was removed, excess material was removed from the surface, and the surface was ground smooth. Release the residual stress inside; place it in a container, then place the container in a liquid nitrogen pool (-196℃), leave it for 1 hour, then take it out, then place the container in an annealing furnace at a temperature of 500℃, keep it at that temperature for 1 hour, and take it out. This is one cold and hot cycle; repeat the cold and hot cycle 5 times to obtain an impact-resistant polycrystalline diamond composite sheet with low residual stress.

[0067] Comparative Example 1 This comparative example relates to a method for preparing a polycrystalline diamond composite sheet, wherein the obtained polycrystalline diamond composite sheet comprises, in the thickness direction: a polycrystalline diamond layer and a cemented carbide layer; In the cemented carbide layer, the volume fraction of tungsten carbide is 79.2%, and the volume fraction of the metallic binder phase is 20.8%. The polycrystalline diamond layer comprises diamond and a metal binder phase, with the diamond volume fraction being 97% and the metal binder phase volume fraction being 3%. The metal binder phase is cobalt powder.

[0068] The preparation method of this comparative polycrystalline diamond composite sheet includes the following specific steps: Weigh out the powder raw materials for the polycrystalline diamond layer and mix them for later use; the powder raw materials for the polycrystalline diamond layer include: diamond powder A with a median particle size of 15μm, diamond powder B with a median particle size of 2μm, and metal binder powder with a median particle size of 2μm; by volume ratio, diamond powder A: diamond powder B: metal binder powder = 73:24:3. Polycrystalline diamond composite sheets were prepared by loading polycrystalline diamond powder into a metal cup, flattening and compacting it to a height of 2 mm, then loading a sintered gradient transition layer block, followed by cemented carbide (20 mm thick), covering with a metal cap, and compacting it with a press. The resulting composite sheet was then assembled with salt tubes, graphite tubes, pyrophyllite, and other components into a composite block. The composite block was placed in the synthesis chamber of a six-sided press and subjected to high-temperature, high-pressure sintering at a pressure of 6.5 GPa, a temperature of 1500℃, and a sintering time of 10 minutes. After sintering, the composite sheet was removed, excess material was removed from the surface, and the surface was ground to a smooth finish, yielding the polycrystalline diamond composite sheet product.

[0069] Detection and Analysis Examples 1 and 2 respectively prepared impact-resistant polycrystalline diamond composite sheets with low residual stress and gradient transition layers containing two and three sublayers, respectively. The microstructures are as follows: Figure 1 As shown, Figure 1 -a corresponds to Example 1. Figure 1 -b corresponds to Example 2; the dark area in the figure represents the diamond phase, and the light area represents the binder phase and tungsten carbide. It can be seen from the figure that from the polycrystalline diamond layer towards the cemented carbide layer, the diamond phase decreases layer by layer, while the binder phase and tungsten carbide increase layer by layer, exhibiting a clear layered distribution. Figure 1 -a has two transition layers between the polycrystalline diamond layer and the cemented carbide layer. Figure 1 The presence of three transition layers between the polycrystalline diamond layer and the cemented carbide layer in -b indicates that the method of the present invention can obtain a polycrystalline diamond composite sheet product with a layered structure.

[0070] The residual stress on the surface of the polycrystalline diamond layer of the polycrystalline diamond composite sheets obtained in Examples 1-3 and Comparative Example 1 was analyzed by Raman spectroscopy, and a drop hammer impact test was performed (T / CMTBA 2005.2-2024 Test methods for diamond or cubic boron nitride composite sheets, Part 2: Impact toughness). The results are shown in Table 1.

[0071] Table 1. Residual stress and impact toughness test results of polycrystalline diamond composite sheets in the examples and comparative examples. The results in Table 1 show that the surface residual stress of the polycrystalline diamond composite sheet obtained by the present invention is significantly reduced compared with that of traditional PDC, and the impact toughness is greatly improved.

[0072] Obviously, the described embodiments are only a part of the embodiments of this invention, not all of them. Those skilled in the art can make improvements or modifications based on the embodiments of this invention. Any other embodiments resulting from modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this invention are within the scope of protection of this invention.

Claims

1. A method for preparing an impact-resistant polycrystalline diamond composite sheet with reduced residual stress, characterized in that, include: The polycrystalline diamond layer powder raw material, gradient transition layer block, and cemented carbide are compacted to form a sheet; the sheet is assembled into a composite block in a six-sided top press and sintered at high temperature and high pressure at 5GPa~8GPa and 1300~1700℃; after sintering, it is alternately placed in a cold environment and a hot environment for more than two cycles to obtain the final product; the resulting polycrystalline diamond composite sheet includes, in sequence: a polycrystalline diamond layer, a gradient transition layer, and a cemented carbide layer. The cold environment is -180℃ to -210℃; the hot environment is 400℃ to 800℃. The polycrystalline diamond layer contains more than 90% diamond by volume; the polycrystalline diamond layer also includes a metallic binder phase. The main components of the gradient transition layer are diamond, tungsten carbide and a metal binder phase.

2. The method for preparing the impact-resistant polycrystalline diamond composite sheet with reduced residual stress according to claim 1, characterized in that, The powder raw materials of the polycrystalline diamond layer include: diamond powder A with a median particle size of 10μm to 20μm, diamond powder B with a median particle size of 1μm to 5μm, and metal binder phase powder.

3. The method for preparing the impact-resistant polycrystalline diamond composite sheet with reduced residual stress according to claim 2, characterized in that, In the powder raw material of the polycrystalline diamond layer, the total volume fraction of diamond powder A and B is greater than 90%; the volume fraction of the metal binder phase powder is less than 10%; and the volume ratio of diamond powder A to diamond powder B in the powder raw material of the polycrystalline diamond layer is 2~6∶1.

4. The method for preparing the impact-resistant polycrystalline diamond composite sheet with reduced residual stress according to claim 1, characterized in that, The gradient transition layer can be subdivided into 2 to 5 sub-layers according to its composition. The sub-layers closer to the polycrystalline diamond layer have a higher diamond content and a lower content of tungsten carbide and metal binder phase. The sub-layers closer to the cemented carbide layer have a lower diamond content and a higher content of tungsten carbide and metal binder phase.

5. The method for preparing the impact-resistant polycrystalline diamond composite sheet with reduced residual stress according to claim 4, characterized in that, The content of each component in each sublayer conforms to the following formula: ; in, The total number of sub-layers is denoted by , with the sub-layer closest to the polycrystalline diamond layer designated as the first sub-layer, and all sub-layers are numbered sequentially. The sequence number of the sub-layer. Not greater than Positive integers; For the first Volume fraction of a certain component in a sublayer This represents the volume fraction of this component in the polycrystalline diamond layer. This represents the volume fraction of this component in the cemented carbide layer.

6. The method for preparing the impact-resistant polycrystalline diamond composite sheet with reduced residual stress according to any one of claims 1 to 5, characterized in that, The method for preparing the gradient transition layer block is as follows: first, a green blank is formed by printing using a binder spraying additive manufacturing process, and then debinding and densification are achieved by vacuum hot pressing sintering to obtain the gradient transition layer block.

7. The method for preparing the impact-resistant polycrystalline diamond composite sheet with reduced residual stress according to claim 6, characterized in that, The raw materials used in the binder spraying additive manufacturing process include: diamond powder with a median particle size of 10μm to 20μm, tungsten carbide powder with a median particle size of 1.2μm to 2.0μm, and metal binder phase powder with a median particle size of 1μm to 5μm.

8. The method for preparing the impact-resistant polycrystalline diamond composite sheet with reduced residual stress according to claim 6, characterized in that, The temperature for vacuum hot pressing sintering is 750~850℃.

9. The method for preparing an impact-resistant polycrystalline diamond composite sheet with reduced residual stress according to claim 2 or 7, characterized in that, The metal binder powder is a cobalt-based alloy powder with a median particle size of 1μm to 5μm.

10. The method for preparing the impact-resistant polycrystalline diamond composite sheet with reduced residual stress according to claim 1, characterized in that, The main component of the metal binder phase is cobalt, and by mass percentage, it also includes: nickel 10%~30%, iron 5%~10%, chromium less than 5%, titanium less than 5%, and boron less than 2%. In the cemented carbide, the mass fraction of cobalt is 10%~15%; The thickness of the polycrystalline diamond layer is 2~4mm; the thickness of the gradient transition layer is 1~3mm; and the thickness of the cemented carbide layer is 5~20mm. The single placement time in a cold environment is 0.5~2h; the single placement time in a hot environment is 0.5~2h; and the high-temperature and high-pressure sintering time is 5~20 minutes.